SIMULASI SISTEM PRODUKSI DI INDUSTRI CAT (STUDI KASUS: UNIT PRODUKSI PT. ABC) - Setiawan, Yohanes; Prasetyo, Waluyo (Journal Knowledge Industrial Engineering (JKIE), 2020)
Productivity in the production process is very influential and become a benchmark for success in every industry. Healthy productivity can increase customer satisfaction because the waiting time for production is not too long from the expected target. The need for improvement in the system is one way to increase production at PT ABC. From the observations results showed the activity percentage of production administration operator were very high. It was at 98.727%. Production per day was less than the company target, the expected target was 40 batches per day, but in fact, it only produced 35 batches average per day. There were three proposed scenarios to fix the performance at Production Unit PT ABC. The Third Scenario was the choice that had highest result for daily production, while Scenario Second was the choice with the highest results if using weekly and annual running times references.